A positive perspective to implementation of a gender equality plan: a question of design, time and participation - Barros, Victor Freitas Azeredo (2018)
This paper describes the initial steps of a project developed with the aim of fostering diversity and the gender equality at the University of Minho, with a particular focus on the school of engineering. The project follows the actionresearch method, starting by gathering the perspectives of the various organizational participants (academics, nonacademics, researchers, and students). The insights emerging from the collected information supported the definition and the prioritization of actions and activities of the Gender Equality Plan. Four levels of intervention were considered: Human Resources and Management Practices, Research Content and Delivery, Teaching and Students’ Services and Institutional Communication, under the EQUAL-IST Project (Gender Equality Plans for Information Sciences and Technology Research Institutions). The techniques used to gather the supporting information included interviews with decision makers, as well as focus groups with students, teachers, and academic staff at the School of Engineering. From the analysis of the gathered information emerged a set of challenges and opportunities to improve gender equality. The Gender Equality Plan (GEP) now being implemented at the university addresses the identified challenges and integrates actions to seize the opportunities to achieve greater gender equality. GEP was designed in line with 3 main goals: raise awareness, implement structural changes and engage stakeholders in mind-set change.